Cancer in Africa 2018: The role of infections. Issue 8 (2nd August 2019) - Parkin, Donald M.; Hämmerl, Lucia; Ferlay, Jacques; Kantelhardt, Eva J.
Abstract : We estimate the fractions of cancer attributed to infections in Africa in 2018. The number of new cancer cases occurring was taken from Globocan2018 with some additional estimations based on data from African population‐based registries. Population attributable fractions were calculated using prevalence of infection and relative risk in exposed vs . nonexposed. The greatest share of infection‐associated cancers is due to the human papillomaviruses (12.1% of all cancers in Africa and 15.4% in sub‐Saharan Africa [SSA]); of these, cervical cancer is by far the most common. Kaposi sarcoma‐associated herpesvirus is responsible for 3.1% of all cancers in Africa, the hepatitis viruses (B and C) for 2.9% and Helicobacter pylori for 2.7% (non‐Cardia Gastric cancer and primary gastric lymphomas). Two percent of cancers are attributable to the Epstein–Barr virus, Schistosoma haematobium increases the risk of bladder cancer resulting in 1.0% of all cancers. HIV‐related NHL and squamous cell carcinoma of the conjunctiva account for 0.6% of cancers. Altogether 24.5% of cancers in Africa and 28.7% in SSA are due to infectious agents. Infections are by far the most common cancer risk factor for cancer in Africa—the traditional risk factors (smoking, alcohol and unhealthy diet) probably cause only one in eight cancers in Africa. Prevention should focus on those infectious diseases preventable through vaccination (HPV and hepatitis B) which could reduce two‐thirds of the burden. Helicobacter pylori and schistosomiasis are treatable with antibiotics and praziquantel, with a potential reduction of one in eight infection‐associated cancers. Abstract : What's new? Infectious agents are a significant cause of cancer in Africa. In the present study, the authors took advantage of new national cancer estimates published in Globocan2018 to determine the current burden of infection‐associated cancers in Africa. Analyses show that most infection‐associated cancers are due to human papillomaviruses. Herpes virus, hepatitis B and C viruses, Helicobacter pylori, and Epstein‐Barr virus were other important infectious causes of cancer. In total, nearly 30 percent of cancers in sub‐Saharan Africa were related to infection, a finding that is of major significance for cancer control efforts, particularly vaccination and other strategies to prevent infection.